2011
DOI: 10.1080/01635581.2011.538486
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Effect of Dietary Fiber Phenolic Compounds Ferulic Acid andp-Coumaric Acid on the Cell Cycle of Caco-2 Cells

Abstract: Epidemiological and animal studies have shown that dietary fiber is protective against the development of colon cancer. Dietary fiber is a rich source of the hydroxycinnamic acids ferulic acid (FA) and p-coumaric acid (p-CA), which both may contribute to the protective effect. We have investigated the effects of FA and p-CA treatment on global gene expression in Caco-2 colon cancer cells. The Caco-2 cells were treated with 150 μM FA or p-CA for 24 h, and gene expression was analyzed with cDNA microarray techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 49 publications
5
96
1
Order By: Relevance
“…Dietary fiber is an important component in a healthy diet, and a strong association between its intake and decreased incidence of colon cancer has been evidenced in several studies [12]. Chemotherapy is an effective way to treat many types of cancers, but the cost of treatment is a major public health concern in developing countries.…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fiber is an important component in a healthy diet, and a strong association between its intake and decreased incidence of colon cancer has been evidenced in several studies [12]. Chemotherapy is an effective way to treat many types of cancers, but the cost of treatment is a major public health concern in developing countries.…”
Section: Colon Cancermentioning
confidence: 99%
“…Additionally, Janicke et al [12] have investigated the effects of FA and p-CoA treatment on global gene expression in Caco-2 colon cancer cells. They have found that FA and p-CoA treatment delayed cell cycle progression and the expressions of a number of genes involved in centrosome assembly, such as RABGAP1 and CEP2, were upregulated by FA treatment as well as the gene for the S phase checkpoint protein SMC1L1 regulation, a total of 517 genes were significantly affected by FA and 901 by p-CoA.…”
Section: Role Of Phenolic Acids On Colon Cancermentioning
confidence: 99%
“…The strong antioxidant character of FA is attributed to its unsaturated side chain and phenolic nucleus that spontaneously forms resonance stabilized structures, thus making it an effective antiproliferative agent. FA is a dietary phytochemical that is known to possess antitumor activities against several types of cancers such as colon, gastric, breast and cervical cancers (Janicke et al 2011; Electronic supplementary material The online version of this article (doi:10.1007/s13204-015-0502-y) contains supplementary material, which is available to authorized users. Kampa et al 2004;Kyoungho et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…15 To further stabilize glucagon at alkaline pH, we became interested in the potential use of ferulic acid, which has been reported to minimize aggregation of the Alzheimer's peptide, amyloid-beta. 22,23 Ferulic acid is found in various foods and beverages, [24][25][26] and is reported to have neuroprotective, 27 antineoplastic, 28,29 and antihypertensive 30,31 actions due to its antioxidant properties. Due to its beneficial effects on inhibiting peptide aggregation, we investigated ferulic acid for its ability to stabilize glucagon.…”
mentioning
confidence: 99%